The role of FoMO in skincare products endorsed by social media influencers in Indonesia - Christoper Hendrata; Dudi Anandya; Indarini (Faculty of Business and Economics, University of Surabaya, 2025)
This study aims to analyze the role of Fear of Missing Out (FoMO) in influencing the purchase intention of skincare products in Indonesia. The type of research used is basic research. This research is quantitative research using primary data, distributed through questionnaires with N = 178. Target respondents who fill out the questionnaire are users of skincare products in the last 1 year. Data processing using the Structural Equation Modeling (SEM) method with the help of SPSS and AMOS software. Results show significant positive effects: imitation of influencers on social comparison (β = .485, p < .001) and on materialism (β = .428, p < .001); social comparison on FoMO (β = .570, p < .001) and on materialism (β = .287, p < .001); FoMO on buying intention (β = .601, p < .001); and materialism on buying intention (β = .254, p < .001). These findings provide insights for skincare companies in Indonesia to utilize relevant influencers to create emotional and social appeal to increase consumer purchase intention.